2018
DOI: 10.1029/2018gl079174
|View full text |Cite
|
Sign up to set email alerts
|

Role of Greenland Sea Gyre Circulation on Atlantic Water Temperature Variability in the Fram Strait

Abstract: Atlantic Water (AW) transported from the Nordic Seas is the major source of oceanic heat to the Arctic Ocean. Based on results from the TOPAZ reanalysis, a regional coupled ice‐ocean data assimilation system, we show that interannual variability of AW temperature in the Fram Strait (FS) is associated with the strength of the Greenland Sea gyre (GSG) circulation. The response of the GSG to the anomalous wind stress curl over the Nordic Seas modifies the AW inflow and thus influences the variability of AW temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 41 publications
3
50
0
Order By: Relevance
“…The barotropic stream function is here defined as ψ=eastwestvdx,1emu=ψy1em&1emv=ψx, where u and v are the depth‐integrated currents in the x and y directions. As previously shown by Aagaard (), Nøst and Isachsen (), and Chatterjee et al (), the leading mode features a barotropic cyclonic circulation in the Nordic Seas. Consequently, the area‐average barotropic stream function over the central Nordic Seas (bounded by 66–76° N, 15° W to 10° E) can be used as an indicator of the strength of the Nordic Seas gyre circulation.…”
Section: Resultsmentioning
confidence: 99%
“…The barotropic stream function is here defined as ψ=eastwestvdx,1emu=ψy1em&1emv=ψx, where u and v are the depth‐integrated currents in the x and y directions. As previously shown by Aagaard (), Nøst and Isachsen (), and Chatterjee et al (), the leading mode features a barotropic cyclonic circulation in the Nordic Seas. Consequently, the area‐average barotropic stream function over the central Nordic Seas (bounded by 66–76° N, 15° W to 10° E) can be used as an indicator of the strength of the Nordic Seas gyre circulation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the warmer‐than‐expected WSC cannot be explained by regional air temperatures. It could be instead that the WSC's faster‐than‐expected speed during Yermak Pass Branch pulses reduced atmospheric cooling and mixing with surrounding water masses (Chatterjee et al, ). Chatterjee et al () found that warm WSC anomalies were associated with a faster current resulting from anomalously positive wind stress curl over the Nordic Seas and a stronger Greenland Sea Gyre.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It could be instead that the WSC's faster‐than‐expected speed during Yermak Pass Branch pulses reduced atmospheric cooling and mixing with surrounding water masses (Chatterjee et al, ). Chatterjee et al () found that warm WSC anomalies were associated with a faster current resulting from anomalously positive wind stress curl over the Nordic Seas and a stronger Greenland Sea Gyre. The most common atmospheric types during Yermak Pass Branch pulses were cyclonic systems bringing wind from the E‐NE‐N to Svalbard, matching the signature of a cyclone moving from the Greenland Sea to the Barents Sea.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…We found that the circulation patterns from high‐resolution models (Hattermann et al, ; Koenig et al, ; Wekerle et al, ) agree well with our observations, especially in pointing out the importance of the YPB for AW transport into the Arctic. The strength and pathways of AW flow around Svalbard are forced by multiple factors: the large‐scale oceanic and atmospheric circulation system (Chatterjee et al, ; Kawasaki & Hasumi, ), the local wind field (Inall et al, ), topography, instabilities, and eddies (Hattermann et al, ; von Appen et al, ; Wekerle et al, ). The average large‐scale AW flow is confined to slopes, plateaus, and trenches, implying that the bottom topography is a major controlling factor.…”
Section: Discussionmentioning
confidence: 99%
“…The average large‐scale AW flow is confined to slopes, plateaus, and trenches, implying that the bottom topography is a major controlling factor. However, the strength of the three AW branches likely varies with time and season and is related to external forcing such as the strength of the North Atlantic gyres, the wind field, and the instability of the WSC and the rate of eddy formation (Chatterjee et al, ; Kawasaki & Hasumi, ; Wekerle et al, ).…”
Section: Discussionmentioning
confidence: 99%